Bone Metabolism in the Healing Process of Lumbar Interbody Fusion: Temporal Changes of Bone Turnover Markers. Issue 23 (1st December 2021) - Hyakkan, Ryota; Kanayama, Masahiro; Takahata, Masahiko; Oha, Fumihiro; Hashimoto, Tomoyuki; Iwasaki, Norimasa
Abstract : Study Design: Prospective longitudinal study. Objective: The aim of this study was to evaluate temporal changes of bone turnover markers (BTMs) after lumbar spinal fusion in patients without osteoporosis. Summary of Background Data: Radiological studies are the standard method to monitor bony fusion, but they do not allow a timely assessment of bone healing. BTMs react rapidly to changes in bone metabolism during fusion process and could be an additional tool to monitor this process. Methods: A total of 78 nonosteoporosis patients who had undergone one- or two-level transforaminal lumbar interbody fusion were included. Fusion status was assessed using computed tomography sagittal and coronal images. Serum levels of bone-specific alkaline phosphatase (BAP), procollagen type 1 amino-terminal propeptide (P1NP), and osteocalcin (OC) were measured to assess bone formation, and tartrate-resistant acid phosphatase 5b (TRACP-5b) was measured to assess bone resorption. Serum samples were obtained before surgery and at 1, 2, 4, 8, 13, 26, 39, and 52 weeks after surgery. Results: A solid fusion was achieved in 71 of 78 patients (91%), and seven patients resulted in pseudarthrosis. In the fusion group, the level of all BTMs once decreased at 1 postoperative week. Then, BAP and P1NP reached a peak at 4 weeks after surgery, and TRACP-5b and OC peaked at 8 weeks. Thereafter, the level of P1NP and TRACP-5b gradually got closer to the baseline over a year, and BAP kept high until 52 postoperative weeks. In the pseudarthrosis group, peak level of BTMs was significantly higher and the increased level of BAP and P1NP was kept until 52 weeks. Conclusion: The present study demonstrated dynamics of BTMs after lumbar spinal fusion in patients without osteoporosis. These normal population data contribute as a baseline to evaluate the effect of osteogenic agents on bone metabolism after spinal fusion. Level of Evidence: 2